Flexible mating system in distylous populations of Psychotria carthagenensis Jacq. (Rubiaceae) in Brazilian Cerrado - Faria, Rogério Rodrigues; Ferrero, Victoria; Navarro, Luis; Araujo, Andréa Cardoso (Plant systematics and evolution, 2012)
In family Rubiaceae distyly is very common, and large variation in heterostyly characteristics has been previously documented. Analysis of these variations, even within a species, is very useful to our understanding of the evolutionary process that caused this polymorphism. For this reason, the goal of this study is to investigate the floral morphology and diallelic incompatibility system of three populations of Psychotria carthagenensis. The three studied populations of P. carthagenensis occur in forest fragments in protected areas in an urban matrix in the Municipality of Campo Grande, Mato Grosso do Sul State, Brazil. Reciprocal position of style length and stamen height was found in populations, and in general short-styled flowers were larger than long-styled flowers. All populations presented 1:1 morph ratio between short-styled and long-styled flowers. Regarding breeding system, flowers of P. carthagenensis were self-compatible and compatible within plants of the same morph, and there was no pollen limitation in the populations in any case. In only one of the populations were there differences in the extent of compatibility between morphs, with the long-styled morph being more self-compatible than the short-styled morph. The reproductive strategy of these populations can be advantageous in case of fluctuation of pollinator activity.